2005
DOI: 10.1677/jme.1.01704
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced growth inhibition of human seminoma cells expressing estrogen receptor β and aromatase

Abstract: It is now well established that estrogens participate in the control of normal spermatogenesis and endogenous or environmental estrogens are involved in pathological germ cell proliferation including testicular germ cell tumors. Studying a human testicular seminoma cell line, JKT-1, we show here that 17 -estradiol (10 −12 to 10 −6 M) induced in vitro a significant dose-dependent decrease of cell growth. This antiproliferative effect was maximum after 4 days of exposure at a physiologically intratesticular conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
(46 reference statements)
8
42
0
1
Order By: Relevance
“…Therefore, ERβ, via PTEN, inhibits cell survival, suggesting a collaborative role of these two proteins in mediating E2 action in human seminoma cell line, consistent with the current belief that ERβ may be antiproliferative and tumor-suppressive. 12 In fact, ERα overexpression induced the AKT content, supporting the hypothesis that the presence of ERα is associated with the proliferative effects of estrogens. 36 Reduced AKT activity may induce cell death through apoptosis; however, in our cells, the expression of proapoptotic proteins such as FKHR1, BID and BAX was faint.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Therefore, ERβ, via PTEN, inhibits cell survival, suggesting a collaborative role of these two proteins in mediating E2 action in human seminoma cell line, consistent with the current belief that ERβ may be antiproliferative and tumor-suppressive. 12 In fact, ERα overexpression induced the AKT content, supporting the hypothesis that the presence of ERα is associated with the proliferative effects of estrogens. 36 Reduced AKT activity may induce cell death through apoptosis; however, in our cells, the expression of proapoptotic proteins such as FKHR1, BID and BAX was faint.…”
Section: Discussionmentioning
confidence: 53%
“…11 Conversely, E2 inhibits human embryonal carcinoma cell proliferation in vitro through an ERβ-dependent mechanism. 12 In human testis, gonocytes and adult germ cells 13 mainly express ERβ, while ERβ loss is associated with advanced tumor stage in several cancers. 14 However, the precise role of estrogens/ERs in the biology of TGCTs remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, ESR2, but not ESR1 and androgen receptor (AR), is expressed in gonocytes and spermatogonia (29). It is worth to mention that ESR2 is coexpressed with ESR1 in tumoral seminoma cells, where it may counteract the tumor cell proliferation mediated by ESR1 (30).…”
Section: Testismentioning
confidence: 99%
“…These cell lines are JKT-1 [70,81,90,146] and TCam-2 [59,89]. Gene expression and immunohistochemical profiling have shown that only the TCam-2 cell line is representative for seminoma (Fig.…”
Section: Human Testicular Gctsmentioning
confidence: 99%